The impact of personality and lifestyle on interaction with nature - Abu Bakar, Aisyah; Mohamed Osman, Mariana; Hitam, Mizan (Malaysian Institute Of Planners, 2020)
Awareness on the complex interdepending systems between individuals and their contexts is a fundamental understanding of sustainable well-being. Collectivist beliefs and biospheric values translate the normative behaviours when environmental decisions are being made. Issue: Existing research has limited empirical evidence on the impact of personality and lifestyle (PL) on interaction with nature (IN) for Malaysia. Purpose: This paper aims to verify the statistical predictability of IN based on PL. Approach: Multiple Correlation and Multiple Linear Regression were carried out to assess linear associations and parameters of linear equations to predict IN components based on PL items. Findings: IN components were predictable by the majority of the PL items and ‘feeling affected by the environmental loss of other countries’ was the strongest predictor of IN.